The healthy skeptic : cutting through the hype about your health - Davis, Robert J., 1963- (University of California Press, 2008)
"The Healthy Skeptic explores who the health promoters are - from journalists and celebrities to industry-funded groups and consumer activists - what their motives are, and how they are spinning us in ways we often don't recognize. Robert J. Davis, a health reporter who holds a master's degree in public health and a PhD. in health policy, digs into the science and debunks widely promoted myths and misconceptions about a variety of issues, including cholesterol, sunscreen, superfoods, weight loss, vitamins, disease screening, harmful chemicals, and antiaging remedies."--Jacket